SELECTION OF EFFECTIVE CHEMICALS IN THE FIGHT AGAINST WIDESPREAD RODENTS IN INTENSIVE APPLE ORCHARDS IN THE CONDITIONS OF KHOREZM REGION - Bobojonov Otabek Khakimboy ugli; Rajabova Shohista Zohidovna (Web of Journals Publishing, 2025)
This article deals with protection against common rodent pests in intensive apple orchards in Khorezm region, the use of agrotechnical, biological and chemical methods harmful to the environment and human health, and the fight against rodent pests in apple orchards. is to study the effectiveness of using new chemical preparations.
Keywords: Apple worm, apple fruit eater, drug, method, fungus, pheromone trap.